Extreme weather events and human health in South Africa: implications for climate services - Manyuchi, Albert Edgar (University of the Witwatersrand, Johannesburg, 2022)
Extreme weather events (EWEs), defined as ‘weather events that are rare at a particular place and time of the year’, have increasingly been affecting many countries worldwide (IPCC 2014). The increased occurrence and intensity of EWEs, among other factors, has increased public interest and demand for climate information. More detail is needed on EWEs and how they can be more effectively coupled to climate services in Africa. This study brings a compendium of empirical evidence, conceptual clarity and transdisciplinary approaches to policymakers, researchers and practitioners dealing with these crucial issues. The main aim of this study is to explore the human health effects of EWEs, particularly heat and the delivery of climate services for health in Africa. Through a systematic review, the study examines the potential impacts of heat on human health in Africa. Using a case study approach heathealth effects are evaluated including the status of climate services in the Agincourt subdistrict of South Africa. A novel systems theory-based conceptual framework and an inclusive analytical framework are employed to explore climate services delivery within the context of climate change adaptation. The study produces two main findings. First, EWEs particularly heat, potentially affects human health in Africa by changing mortality and morbidity patterns. In the Agincourt sub-district in particular, heat may be associated with adverse health effects on vulnerable populations, including inter alia the elderly, children and outdoor workers. Despite this, Africa-specific heat-health interventions and policy suggestions are scarce. Second, climate services are generally in embryonic stages of development and climate services for health in Agincourt subdistrict are non-existent. Within the South African context, the main barriers to delivery of climate services for health are paucity of interagency coordination and gaps in meteorological data. One of the key conclusions of the study is that African countries can promote development of climate services to adapt to EWEs such as heat. Heat, and heatwaves, for example, are already affecting populations, and are projected to increase in frequency and intensity with concomitant adverse effects on health outcomes on vulnerable population groups. The three key recommendations from this study are as follows. First, African policymakers and practitioners must avoid a reductionist approach to analysis of EWEs, especially heat impacts and start viewing these as harmful to human health. Therefore, governments must prioritise interventions, create institutions and formulate policy measures to deal with the health effects of heat within their national adaptations plans. Second, African countries must prioritise policy mixes that promote climate services in general and climate services for health in particular. And finally, further policy-science research that generates empirical evidence for African policymakers and practitioners engaged in international negotiations and programmes for climate change adaptation and climate services should be encouraged.
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, University of the Witwatersrand, 2022
Keywords: Climate Change; Climate Services for Health; Heat Events; SDG-13: Climate action